(untitled) (diségno, 2021)
Mining sites represent one of the greatest challenges for territorial regeneration policies in Europe and in the world, often defined, in their spatial-typological connotations, with meanings that generally suggest negative qualities such as episodic fragmented and, at times, degraded spaces, not highlighting their value as ‘cultural landscapes’. Despite a preliminary and non-exhaustive national and regional regulatory framework, the issue of enhancing these areas needs greater attention from the scientific community, especially in respect of the current international scenario. Specifically, due to its numerous concentration of mining areas, the territorial reality of the Campania region deserves particular attention, with the development of an open information system from which to derive a synoptic representation of the state of affairs that integrates the historical-cultural identity with the figurative and perceptive dimension of places.